Participatory citizen science for Relational One Health and Indigenous food sovereignty - Silvia Sarapura-Escobar; Paul Benalcazar; Charlotte Potter; Natalia Berti; Seth Sabourin; Netmizaaggamig Nishnaabeg (Frontiers in Sustainable Food Systems, 2026)
Introduction Food insecurity in First Nations communities in Northern Ontario is shaped by geographic isolation, high transportation costs, colonial disruption of land-based food systems, and environmental change. This paper examines Participatory Citizen Science (PCS) as a community-led, culturally grounded response, drawing on two growing seasons of data from the Braiding Food Systems (BFS) Project, led by the University of Guelph in partnership with the First Nations communities of Red Rock Indian Band (RRIB), Biinjitiwaabik Zaaging Anishinaabek (BZA), and Netmizaaggamig Nishnaabeg (NN) in Northern Ontario. Guided by a Relational One Health (ROH) framework and Two-Eyed Seeing, the project engaged community members as ‘Garden Stewards’ — citizen scientists leading community garden and seed stewardship initiatives. Methods Using a mixed qualitative-descriptive methodology including focus group discussions, semi-structured interviews, participatory workshops, and systematic garden monitoring, the study documents how PCS functioned simultaneously as an epistemic, governance, and food sovereignty practice. Results Findings demonstrate that PCS enabled a progressive realization of Bridging, Braiding, and Weaving — from foundational relationship-building and co-design, through the intertwining of Indigenous and Western knowledge in practice, toward community-led governance of seed lodges and food system decision-making. Garden Stewards evolved from procedural participants to reflexive knowledge producers, disrupting conventional hierarchies between researcher and community. Discussion The study advances understanding of food sovereignty as a relational and epistemic practice enacted through everyday acts of seed selection, intergenerational learning, and land stewardship. Findings have implications for Indigenous data sovereignty, community-led food systems research, and policy addressing food insecurity in remote northern communities.